Diversity of arsenic resistant bacteria from Lonar lake: A meteorite impact alkaline crater lake in Indi - Bagade, A. V.; Paul, D.; Rikame, T.; Giri, A. P.; Dhotre, D.; Pawar, S.; Kodam, K. (Arsenic Research and Global Sustainability - Proceedings of the 6th International Congress on Arsenic in the Environment, AS 2016, 2016)
Lonar lake known for its meteorite impact origin and highly alkaline environment harbors a plethora of diverse organisms. Arsenic transforming microbe diversity from Lonar remains unexplored. We attempted to explore the microorganisms causing arsenic transformation using culture-dependent and independent approaches. Amongst the 67 microbes isolated, Bacillus infantis L4-18 and Bacillus solimangrovi L4-7b could oxidise 15 mM arsenite in 8 days. None of the cultures could reduce arsenate. All the other isolates resisted 2 mM arsenic. In the culture independent approach, microbial diversity revealed Bacteroides (41.9%), followed by Proteobacteria (17.9%), Firmicutes (14.2%), Actinobacteria (13.9%), occurring in the Lonar sediment sample. This study provides foundation to study microbial arsenic biogeochemical cycle along with other biochemical cycles and microbial function in Lonar lake eco system.